Experience and feelings of patients with leprosy from a therapy center in Teresina-PI (Research, Society and Development, 2021)
Objective: to identify the main feelings after the diagnosis of leprosy and the difficulties in carrying out the treatment. Method: This is a descriptive study with a qualitative approach conducted at a Reference Center in the treatment of leprosy patients in the city of Teresina-PI. Eleven patients who underwent leprosy monitoring and treatment participated in the research. Patients aged 18 years or older undergoing treatment with polychemotherapy were included, and only those who had severe disease sequelae were excluded. The results were organized and interpreted according to Bardin's Content Analysis. Results: It was found that some patients had negative feelings when receiving the diagnosis, showing that leprosy remains a difficult and painful experience and it was identified that the main difficulties experienced after the diagnosis were related to food, to locomotion due to the sequelae illness, travel to receive medication at the health unit and adherence to treatment. Conclusion: leprosy patients, despite treatment and cure, still suffer from fears, prejudices, misinformation and especially with the stigma related to the disease, highlighting the importance of health professionals to address issues relevant to the disease and answer questions.